Effect of clindamycin and a live biotherapeutic on the reproductive outcomes of IVF patients with abnormal vaginal microbiota: protocol for a double-blind, placebo-controlled multicentre trial - Niels Uldbjerg; Nina La Cour Freiesleben; Anja Pinborg; Peter Humaidan; Henriette Svarre Nielsen; Thor Haahr; Vibeke Hartvig; Anne-Lis Mikkelsen; Thomas Parks; Jørgen Skov Jensen (BMJ Open)
Introduction Recent studies in in vitro fertilisation (IVF) patients have associated abnormal vaginal microbiota (AVM) with poor clinical pregnancy rates of 6%–9% per embryo transfer. The biological plausibility for this finding is hypothesised to be ascending infection to the endometrium which in turn hampers embryo implantation. New molecular based diagnosis may offer advantages compared to microscopical diagnosis of AVM which has huge inter-study variability ranging from 4 to 38%; however, the important question is whether screening and treatment of AVM would improve reproductive outcomes in IVF patients. Herein, we describe a protocol for an ongoing double-blind, placebo-controlled multicentre trial of IVF patients diagnosed with AVM and randomised in three parallel groups 1:1:1.Methods and analysis This is a drug intervention study where IVF patients will be screened for AVM, using a qPCR assay targeting Atopobium vaginae and Gardnerella vaginalis. If positive, patients will be randomised to one of the three study arms. The first arm consists of clindamycin 300 mg ×2 daily for 7 days followed by vaginal Lactobacillus crispatus CTV-05 until clinical pregnancy scan week 7–9. The second arm consists of clindamycin and placebo L. crispatus CTV-05, whereas patients in the third arm will be treated with placebo/placebo. We used a superiority design to estimate that active treatment in both arms will increase the primary outcome, clinical pregnancy rate per embryo transfer, from 20% to 40%. A potential difference between the two active arms was considered exploratory. With a power of 80% and an alpha at 5%, the sample size is estimated to be 333 patients randomised. A pre-planned interim analysis is scheduled at 167 patients randomised.Ethics and dissemination All patients have to give informed consent. Dissemination of results is ensured in clinical trial agreements whether they be positive or not. Ethics committee, Central Denmark Region approved this protocol.Trial registration number ICH-GCP monitored trial, EudraCT 2016-002385-31; Pre-results.